Pengelolaan Manajemen Keuangan pada Lembaga Pendidikan di SD Negeri 17 Cegek - Amelia Rasyid; Hamdi Abdul Karim (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Financial management in educational institutions in schools is something very important in supporting the quality of education. To realize quality education, professional financial management is needed, so that problems related to school finances can be managed effectively and as efficiently as possible to support a quality learning process. The purpose of this study is to find out how to apply financial management in educational institutions in SD Negeri 17 Cegek. The data collection techniques used in this study were through observation, interviews, and documentation. The data analysis technique uses descriptive analysis. The results of the analysis show that SD Negeri 17 Cegek has implemented professional financial management and in accordance with theory, namely implementing education financing planning, education financing sources, implementation or implementation of education financing, accountability and evaluation of education financing. With these results, overall activities related to financial management management at SD Negeri 17 Cegek are in accordance with the regulations set by the government.